Recovery of Protein Concentrates From Microalgal Biomass Grown in Manure for Fish Feed and Valorization of the By-Products Through Anaerobic Digestion - Hernández, David; Molinuevo-Salces, Beatriz; Riaño, Berta; Larrán-García, Ana M.; Tomás-Almenar, Cristina; García-González, Maria C. (Frontiers in Sustainable Food Systems, 2018)
The recovery of proteins from microalgae is gaining special attention for animal feed applications especially for fish feed, as the costs of aquaculture feeds represent between 40-70% of the costs of the fish produced. Besides, the use of pig manure to growth microalgae biomass could contribute to manure bioremediation and therefore to reduce the environmental impacts of its storage. The objective of this study was to recover protein concentrates from microalgal biomass grown in pig manure, paying especial attention to the quality of the extracted proteins that can be used as feed source for fish, and to the amino acids composition, essential amino acids content and availability. Methane potential of the by-products obtained after protein recovery was also determined in order to fully apply the biorefinery concept to valorize the resulting biomass. Results showed a maximum protein recovery of 54.5 ± 3.2% from initial microalgal biomass. Protein content in the protein concentrate accounted for 84.5 g protein/100 g biomass in total solids (TS) basis. In the case of the amino acids profile from protein concentrate, essential amino acids accounted for 47.5 g /100 g amino acids in TS basis. After protein recovery, the resulting by-products named spent and liquid fraction were anaerobically digested in batch assays, obtaining a maximum methane production of 181 mL CH4/g VS added.